Genetic Diversity and Population Structure of Amphidromous Goby (Stiphodon semoni) in Western Part of Southern Java Waters - Romdon, Ahmad; Simanjuntak, Charles P. H.; Sulistiono; Syahailatua, Augy (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Graphical Abstract Research Highlight The genetic diversity of Stiphodon semoni is high. All populations have high haplotype diversity except for Cimaja. No genetic structure is observed within the populations of semoni. The population of semoni has undergone demographic expansion. Cibareno River has the potential to be a protected area. Abstract Fishing activities negatively impact fish populations, potentially causing a decline in fish stocks. Nevertheless, ensuring diversity and connectivity among populations can mitigate these adverse effects. To evaluate the connectivity of river mouths in the western part of Southern Java waters, we sequenced forty Stiphodon semoni individuals from five populations using mitochondrial cytochrome oxidase subunit 1 as molecular markers. The study revealed that S. semoni populations showed high diversity (0.821), with the population in Cimaja displaying the lowest diversity (0.464). Furthermore, the result of the analysis of molecular variance was a Fst value of 0.0630 with a p-value of 0.22. These results along with the result of the haplotype network indicated no significant genetic differences among these populations. This implies that the river mouths in the western part of Southern Java waters are interconnected. The distribution of mismatches showed a single peak, indicating that the populations have undergone demographic expansion. This information could be valuable for the conservation and management of S. semoni in the western part of the Southern Java waters.